Two-dimensional DOA estimation with a staggered two-parallel linear array for reducing mutual coupling - Liu, Sheng; Zhao, Jing; Wu, Decheng; Xiong, Weizhi; Xia, Linli; Tan, Wenbin (Multidimensional systems and signal processing, 2025)
In this paper, a two-dimensional (2D) direction of arrival (DOA) estimation algorithm with a staggered two-parallel linear array has been proposed. The proposed array consists of two staggered linear arrays, any one of which is determined by two consecutive positive integers. The distance between any two sensors of the proposed array can be larger than half-wavelength of incident signal, so it has strong robustness to mutual coupling. Using this array, a segmented propagator method (PM) algorithm is proposed to get automatic matching 2D DOA estimation. Compared with some similar PM algorithms based on a two-parallel linear array, the proposed segmented PM algorithm has higher estimation accuracy and approaching complexity. Not only that, the proposed algorithm can detect more signals than similar algorithms without using virtual elements. Complexity analysis and simulation results can prove the advantage of the proposed algorithm.